2020
DOI: 10.1038/s41598-020-73352-1
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of L4 coronal tilt relative to C7 plumb line as a predictor for postoperative coronal imbalance in patients with degenerative lumbar scoliosis

Abstract: The study design is case–control. To evaluate the impact of preoperative coronal patterns based on the relationship between orientation of L4 coronal tilt and C7 plumb line on immediate postoperative coronal imbalance in degenerative lumbar scoliosis (DLS) patients. Although lumbosacral fractional curve has been long stressed in correction surgery of DLS, there is paucity of literature focusing on preoperative coronal pattern based on the relationship between orientation of L4 coronal tilt and C7 plumb line an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…This result was confirmed by other authors, who explained it with an inadequate correction of the lumbosacral fractional curve [5,15]. However, while some authors have analyzed the influence of the preoperative trunk shift on the postoperative balance [5,15], and others studied the L4 and L5 tilt [16][17][18], as far as the authors know, there is no study evaluating the correlation of all these preoperative variables (trunk shift, L4 tilt, L5 tilt, and sagittal parameters) on the postoperative balance, providing a comprehensive understanding of the preoperative radiographical risk factors for CIB. The aim of the present study was to elucidate preoperative risk factors for inadequate correction of coronal imbalance and/or creation of new postoperative coronal imbalance (iatrogenic CIB) in patients who undergo surgery for Adult Spinal Deformity (ASD).…”
Section: Introductionsupporting
confidence: 59%
“…This result was confirmed by other authors, who explained it with an inadequate correction of the lumbosacral fractional curve [5,15]. However, while some authors have analyzed the influence of the preoperative trunk shift on the postoperative balance [5,15], and others studied the L4 and L5 tilt [16][17][18], as far as the authors know, there is no study evaluating the correlation of all these preoperative variables (trunk shift, L4 tilt, L5 tilt, and sagittal parameters) on the postoperative balance, providing a comprehensive understanding of the preoperative radiographical risk factors for CIB. The aim of the present study was to elucidate preoperative risk factors for inadequate correction of coronal imbalance and/or creation of new postoperative coronal imbalance (iatrogenic CIB) in patients who undergo surgery for Adult Spinal Deformity (ASD).…”
Section: Introductionsupporting
confidence: 59%
“…It has been suggested that patients with different preoperative CM types can have different surgical outcomes. Zhang et al showed that the incidence of postoperative coronal imbalance was significantly higher in patients with preoperative Obeid type 2 than in those with preoperative Obeid type 1 [ 26 ]. They examined an ASD patient who underwent deformity correction surgery with a posterior-only approach in their case series.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Lewis et al 17 reported the relationship between L4/5 tilt and postoperative CIB. Zhang et al [13][14][15] discovered that the consistency between the C7 PL and L4 tilt direction was associated with CIB. Another study 16 also proposed that the coronal T1 pelvic tilt angle was a practical index to evaluate CBD.…”
Section: Discussionmentioning
confidence: 99%
“…reported the relationship between L4/5 tilt and postoperative CIB. Zhang et al 13–15 . discovered that the consistency between the C7 PL and L4 tilt direction was associated with CIB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation